Modelling of Internal Stresses in Sheet Glass during the Cooling - Benbahouche, Saci; Roumili, Fouad; Sangleboeuf, Jean-Christophe (My University, 2011)
Internal stresses in glass are generated by interactions between thermal contraction, elasticity at low temperatures, viscoelastic flow at higher temperature, and temperature gradients caused by cooling. This work intends to work out calculation program for real temperature distribution and internals stress, and to study their behaviour during the quenching through a flat plate of soda-lime glass from different temperatures
Keywords: Modelling; Internal Stresses; Glass